iMENA : An Innovation Agenda for Jobs - Bell, Simon (World Bank, Washington, DC, 2012)
A critical issue in the Middle East and North Arica (MENA) region is employment, especially for youth and women. Young Arabs have some of the highest unemployment rates in the world, and women are significantly excluded from the job market. Also given high concentrations of poverty is some of our countries (Egypt, Morocco, etc.) inclusive growth focused on creating jobs and economic opportunities for the poor and dispossessed is a key part of the agenda. The recent revolutions have only further highlighted the critical importance of job creation for the region. Yet the region except in some industries and in some countries is unlikely to have a comparative advantage in labor intensive manufacturing Asia.